Stay positive: catalysis with 1, 3, 2-diazaphospholenes. Issue 21 (11th September 2020) - Reed, John H.; Klett, Johannes; Steven, Craig; Cramer, Nicolai
Abstract : Fundamental properties and recent advances in the catalytic application of 1, 3, 2-diazaphospholenes are reviewed, and future directions for the field are presented. Abstract : P -Hydrido 1, 3, 2-diazaphospholenes (DAPs) are a class of nucleophilic molecular hydrides capable of addition to a variety of substrates. They can be turned over with terminal reductants and emerged over the last few years as powerful and versatile catalysts. This review highlights developments made in understanding the chemistry of these unusual compounds and applying them in catalysis. An overview of the synthesis and important structural features of the DAPs is followed by a discussion of methodologies that exploit their chemistry in catalysis, including the rise of enantioselective reductions. We conclude with a brief analysis on the current limitations of the field and discuss how these might be overcome and which directions the field might take in the future.